Genetically determined factors as predictors of radiological change in patients with early symmetrical arthritis. Issue 6866 (5th December 1992) - Emery, P.; Salmon, M.; Bradley, H.; Wordsworth, P.; Tunn, E.; Bacon, P. A.; Waring, R.
Abstract : OBJECTIVE–To determine whether genetic factors associated with established rheumatoid arthritis could, in combination with rheumatoid factor, predict the development of radiological erosions in patients with early symmetrical (rheumatoid-like) arthritis. DESIGN–Prospective study. SETTING–Teaching hospital, early arthritis clinic. SUBJECTS–Forty nine patients with symmetrical polyarthritis attending the early arthritis clinic. MAIN OUTCOME MEASURES–Conserved sequence of DR beta third allelic hypervariable region, sulphoxidation capacity, rheumatoid factor, and development of radiologically determined bone erosions. RESULTS–None of the 49 patients had radiological erosions at presentation but 25 developed these by four years. Patients with the conserved class II major histocompatibility complex (third allelic hypervariable of DR beta 1) genes associated with rheumatoid arthritis had a relative risk for the development of erosions of 1.9 (95% confidence interval 0.8 to 4.5). For poor sulphoxidation the risk was 2.5 (1.1 to 5.6) and for the presence of rheumatoid factor 1.8 (0.9 to 3.7). Of the 33 patients who had two or three of these risk factors, 24 developed erosions, with a relative risk of 11.6 (1.7 to 78.5) compared with only one of the 16 individuals with no or one risk factor. CONCLUSIONS–This preliminary study shows that by using these stable markers it is possible to make clinically useful predictions of outcome in patients with early symmetrical inflammatory arthritis.